The role of the Da'i in Islamic Religious Development - Lovardi Rizky Wirawan; Muhammad Yusuf Mahfudhi; Aji Saka Nusantara; Ivan Eri Danendra; Agil Abiyu Aradhana (International Journal of Islamic Educational Research, 2024)
This research was carried out with the aim of finding out how much influence the Da'i had on the religious knowledge of the village . This research method was carried out by observation and interviews with the people of village X. The results of the research stated that the three Da'i , namely Mr. Rizal, Mr. Dahlan, and Mr. Wildan , had succeeded in bringing significant change and development to village